Corn Cost-Return Budget in Southeast Kansas - Dumler, Troy J.; Shoup, Douglas (My University, 2012)
This publication outlines the expected costs and returns for corn in southeast Kansas.
MF993_2012_12
Keywords: MF993; Economics; Crops; MF